2014
DOI: 10.1097/scs.0000000000000502
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic-Assisted Neck Tissue Expansion in Reconstruction of Facial Burn Injuries

Abstract: Endoscopic-assisted neck tissue expansion is associated with lower complication rate, shorter duration of hospitalization, reduced operative time, earlier initiation of expansion, and faster expansion process. It could be a feasible alternative to open technique in reconstructing facial burns, allowing smaller incision at port site, far placement of tissue expander, and excellent visualization of operation site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Skin soft-tissue expansion is widely used in repairing skin or soft tissue defects induced by various causes, such as incision of congenital giant nevus, scars, tumors, and skin defects after trauma. Following the wide application of expanders, numerous studies have reported an increasing number of expanded skin flap uses (6)(7)(8). However, the use of a flap has also been associated with some complications such as necrosis, infection, and hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…Skin soft-tissue expansion is widely used in repairing skin or soft tissue defects induced by various causes, such as incision of congenital giant nevus, scars, tumors, and skin defects after trauma. Following the wide application of expanders, numerous studies have reported an increasing number of expanded skin flap uses (6)(7)(8). However, the use of a flap has also been associated with some complications such as necrosis, infection, and hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive endoscopic techniques have been described for expander placement. 72,73 Various authors have described attempts to enhance and facilitate the expansion process pharmaceutically. 74,75 Self-inflating osmotic expanders have also recently been described that do not require painful injections for inflation.…”
Section: Future Directionsmentioning
confidence: 99%